AIE Multinuclear Ir(III) Complexes for Biocompatible Organic Nanoparticles with Highly Enhanced Photodynamic Performance. Issue 5 (21st January 2019) - Zhang, Liping; Li, Yuanyuan; Che, Weilong; Zhu, Dongxia; Li, Guangfu; Xie, Zhigang; Song, Nan; Liu, Shi; Tang, Ben Zhong; Liu, Xingman; Su, Zhongmin; Bryce, Martin R.
Abstract: The singlet oxygen ( 1 O2 ) generation ability of a photosensitizer (PS) is pivotal for photodynamic therapy (PDT). Transition metal complexes are effective PSs, owing to their high 1 O2 generation ability. However, non‐negligible cellular toxicity, poor biocompatibility, and easy aggregation in water limit their biomedical applications. In this work, a series of red‐emitting aggregation‐induced emission (AIE) Ir(III) complexes containing different numbers of Ir centers (mono‐, di‐, and trinuclear) and the corresponding nanoparticles (NPs) AIE‐NPs, are designed and synthesized. The increase of 1 O2 generation ability is in line with the increasing number of Ir centers. Compared with the pure Ir(III) complexes, the corresponding NPs offer multiple advantages: (i) brighter emission; (ii) higher phosphorescence quantum yields; (iii) longer excited lifetime; (iv) higher 1 O2 generation ability; (v) better biocompatibility; and (vi) superior cellular uptake. Both in vitro and in vivo experiments corroborate that AIE‐NPs with three iridium centers possess potent cytotoxicity toward cancer cells and effective inhibition of tumor growth. To the best of knowledge, this work is the first example of NPs of multinuclear AIE Ir(III) complexes as PSs for enhanced PDT. This study offers a new method to improve the efficiency of PSs for clinical cancer treatments. Abstract : Red‐emitting aggregation‐induced emission Ir(III) complexes containing different numbers of Ir centers (mono‐, di‐, and trinuclear) and the corresponding nanoparticles are synthesized and studied as photosensitizers. In vitro and in vivo experiments demonstrate that the nanoparticles with three iridium centers exhibit potent cytotoxicity toward cancer cells and effectively inhibit tumor growth.